2020
DOI: 10.1016/s2352-3026(20)30217-9
|View full text |Cite
|
Sign up to set email alerts
|

Haematological characteristics and risk factors in the classification and prognosis evaluation of COVID-19: a retrospective cohort study

Abstract: Summary Background COVID-19 is an ongoing global pandemic. Changes in haematological characteristics in patients with COVID-19 are emerging as important features of the disease. We aimed to explore the haematological characteristics and related risk factors in patients with COVID-19. Methods This retrospective cohort study included patients with COVID-19 admitted to three designated sites of Wuhan Union Hospital (Wuhan, China). Demographic, clinical, labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
491
9
26

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 465 publications
(568 citation statements)
references
References 30 publications
42
491
9
26
Order By: Relevance
“…Han et al [5] also reported that there was no significant difference in PT between patients with different levels of severity of COVID-19 and healthy controls. However, more studies reported that severe patients had significantly prolonged PT compared with non-severe patients [16][17][18]. In addition, two studies on COVID-19 indicated that non-survivors had higher PT levels than survivors [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…Han et al [5] also reported that there was no significant difference in PT between patients with different levels of severity of COVID-19 and healthy controls. However, more studies reported that severe patients had significantly prolonged PT compared with non-severe patients [16][17][18]. In addition, two studies on COVID-19 indicated that non-survivors had higher PT levels than survivors [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients had good results with treatment, while the elderly patients and those with chronic diseases usually had poor prognoses. Although most patients with COVID-19 had mild and moderate symptoms, severe and critically ill patients progressed rapidly to acute respiratory failure, ARDS, metabolic acidosis, coagulopathy, septic shock, and MOF (7,(40)(41)(42). The autopsy report in the journal The Lancet Respiratory Medicine showed typical ARDS-like lung injury with lymphocyte infiltration, liver injury with moderate micro-vesicular steatosis, mild lobular and portal activity (43).…”
Section: Clinical Pathological and Serological Manifestations In Comentioning
confidence: 99%
“…In fact, standard coagulation parameters, including elevated levels of D-Dimer (DD) (DD ≥ 0.5 mg/L), are often found in patients in patients with poor prognosis [ 14 ]. Despite the exact pathophysiological mechanisms needs to be further investigated, assessing the risk of thrombosis in COVID-19 patients is critical to improve the clinical management in terms of anticoagulation therapy [ [23] , [24] , [25] , [26] ].…”
Section: Hematological Response During Covid-19mentioning
confidence: 99%